Pengembangan Karakter Toleran dalam Problematika Ikhtilaf Mazhab Fikih - Muammar Bakry (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The discourse of ikhtilaf is an undeniable reality. Consequently, to put forward opinion in the same agreement will likely to contradict with human nature which has been determined by Allah SWT. The different thoughts among the ulamas are actually good phenomena in Islamic teaching, which lead to Isla to be more variativ. Fiqh minded which are triggering into in-tolerancy dan discriminative character toward the other groups should be critically understood as an historical product which is very possible to be changed. This paper proposes tolerant character development in facing the difference among Islamic thought schools (mazhab fiqh) through four scopes of character education: that are, spiritual and emotional development, intellectual develompmet, physical and kinesthetic development, and affective and creativity development. These four characters will give per-ception to address the differences (ikhtilaf) among Muslims and eventually come to either tolerant or in-tolerant character.